Antibiotic adjuvants: synergistic tool to combat multi-drug resistant pathogens - Kumar, Vikram; Yasmeen, Nusrath; Pandey, Aishwarya; Ahmad Chaudhary, Anis; Alawam, Abdullah S.; Ahmad Rudayni, Hassan; Islam, Asimul; Lakhawat, Sudarshan S.; Sharma, Pushpender K.; Shahid, Mohammad (Frontiers in Cellular and Infection Microbiology, 2023)
The rise of multi-drug resistant (MDR) pathogens poses a significant challenge to the field of infectious disease treatment. To overcome this problem, novel strategies are being explored to enhance the effectiveness of antibiotics. Antibiotic adjuvants have emerged as a promising approach to combat MDR pathogens by acting synergistically with antibiotics. This review focuses on the role of antibiotic adjuvants as a synergistic tool in the fight against MDR pathogens. Adjuvants refer to compounds or agents that enhance the activity of antibiotics, either by potentiating their effects or by targeting the mechanisms of antibiotic resistance. The utilization of antibiotic adjuvants offers several advantages. Firstly, they can restore the effectiveness of existing antibiotics against resistant strains. Adjuvants can inhibit the mechanisms that confer resistance, making the pathogens susceptible to the action of antibiotics. Secondly, adjuvants can enhance the activity of antibiotics by improving their penetration into bacterial cells, increasing their stability, or inhibiting efflux pumps that expel antibiotics from bacterial cells. Various types of antibiotic adjuvants have been investigated, including efflux pump inhibitors, resistance-modifying agents, and compounds that disrupt bacterial biofilms. These adjuvants can act synergistically with antibiotics, resulting in increased antibacterial activity and overcoming resistance mechanisms. In conclusion, antibiotic adjuvants have the potential to revolutionize the treatment of MDR pathogens. By enhancing the efficacy of antibiotics, adjuvants offer a promising strategy to combat the growing threat of antibiotic resistance. Further research and development in this field are crucial to harness the full potential of antibiotic adjuvants and bring them closer to clinical application.